Teacher’s Asynchronous Written Corrective Feedback in Online Esp Classroom: Students' Perceptions - Sibuea, Todo; Rahmawati, Irma (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
The current study investigates the types and focus of an EFL teacher’s corrective feedback and the students’ perceptions about their teacher’s feedback. This study adopts a mixed-method approach by combining quantitative and qualitative data to examine the teacher’s electronic asynchronous feedback. The data for this study were collected by conducting online observations of the teacher’s classes which were mediated by a Learning Management System (LMS), an online survey distributed to the course’s students and a semi-structured interview with selected participants. The respondents who filled out the survey were 17 undergraduate students from the communication department at a private university in Jakarta, Indonesia. The students took a mandatory English for Specific Purposes (ESP) course and participated in this study voluntarily. The findings revealed that the ESP teacher preferred providing direct and focused feedback in her online classes. The focus of her feedback was oriented toward the processes of learning and the levels of self-regulation. In terms of perception, the part-time students perceive the teacher’s direct and focused feedback as helpful in indicating their weak areas in L2 competency and appropriate for online courses.